Effect of sulphur and iron levels on yield and nutrient content and uptake of Clusterbean [Cyamopsis tetragonoloba (L.) Taub.] in arid region of Rajasthan - Tiwari, D.K.; Pareek, B.L.; Singh, Bahadur (Annals of Agricultural Research, 2017)
A field experiment was conducted on clusterbean during kharif 2012 at Agronomy farm of SwamiKeshwanand Rajasthan Agriculture University, Bikaner. There were four levels of sulphur (0, 20,40 and 60 kg S/ha) and four levels of iron (0, 2.5, 5 and 7.5 kg Fe/ha) carried out to study the effectof sulphur and iron on yield and quality of clusterbean. The results indicated that application of 40kg S/ha significantly increased yield, nutrient content and uptake of cluster bean and remained atpar with 60 kg S/ha. Result further indicated that the application of iron @ 5 kg/ha significantlyincreased seed, stover and biological yield, nutrient content of cluster bean and remained at parwith 7.5 kg Fe ha–1. However, S and Fe uptake in seed and straw and their total uptake significantlyhigher recorded with 60 kg S/ha and 7.5 kg Fe/ha over all other treatments.